Investigating the effect of selected antiretroviral therapies on serum testosterone and testicular microstructure of Wistar rats - Edagha IA; Umoh VA; Peter AI; Asuquo IE; Udofot E; Archibong KE (Ibom Medical Journal, 2021)
Background: Highly active antiretroviral therapies (HAARTs) and other antiretroviral therapies (ARTs) are widely used in the management of human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) as well as repurposing for other infectious conditions despite their reported toxicities. We investigated the gonado-toxicities of two HAARTs and five ARTs in vivo model. Materials and methods: Forty adult male Wistar rats were allotted into eight groups; where Group 1 served as normal control (NC) and received 5 mL distilled water per kg, while Groups 2 to 8 received (Efavirenz+Lamivudine+Tenofovir disoproxil fumarate [ELT 17.14 mg]), (Lamivudine+Nevirapine+Zidovudine [LNZ 9.28 mg]), (Abacavir+Lamivudine [AL 12.86 mg]), (Lamivudine+Zidovudine [LZ 6.43 mg]), (Fumarate de tenofovir disoproxil+Lamivudine [TL 8.57 mg]), (Atazanavir+Ritonavir [AR 5.71 mg]) and (Liponavir+Ritonavir [LR 3.57 mg]) per kg body weight respectively at therapeutic doses via oral route for 30 days, and thereafter sacrificed under anesthesia injection. Blood was obtained via cardiac puncture for hormonal assay, while testes were dissected out for histological assessments. Results: Testosterone concentrations significantly (p < 0.05) declined in the HAART and ART-administered groups compared to NC. Testicular microstructure demonstrated mild to moderate degeneration of the germinal epithelium in the HAART- and ART- groups compared to NC. Conclusion: ELT was less gonadotoxic compared with LNZ, while LZ was the most gonadotoxic ART based on severity of alterations in the testicular hormone and microstructure.